2018
DOI: 10.3329/bsmmuj.v11i2.36629
|View full text |Cite
|
Sign up to set email alerts
|

Adiposity indicators lipid accumulation product and triglyceride-glucose index as alternate criteria for the diagnosis of metabolic obesity in adult

Abstract: Obesity is a medical condition in which excess body fat has been accumulated to such an extent that it can cause a negative impact on health (World Health Organization, 2014). 1 The body mass index (BMI) is most commonly used to classify overweight and obesity. BMI is calculated by dividing a person's weight in kilogram with the square of his/her height in meter (kg/m 2 ).Recently, the concept of metabolic health status, apart from obesity, has gained much significance. 2 A number of studies have been identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
(14 reference statements)
0
2
0
Order By: Relevance
“…Studies in China [17] and Bangladesh [18] found TyG to be one of the best surrogate markers for determining MetS. However, they also found LAP and the visceral adiposity index (VAI) to be efficacious in middle-aged and elderly Chinese [18]. The results were similar to those obtained in the Korean population [19].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Studies in China [17] and Bangladesh [18] found TyG to be one of the best surrogate markers for determining MetS. However, they also found LAP and the visceral adiposity index (VAI) to be efficacious in middle-aged and elderly Chinese [18]. The results were similar to those obtained in the Korean population [19].…”
Section: Introductionmentioning
confidence: 55%
“…Some of these markers have been analyzed in Asian countries. Studies in China [17] and Bangladesh [18] found TyG to be one of the best surrogate markers for determining MetS. However, they also found LAP and the visceral adiposity index (VAI) to be efficacious in middle-aged and elderly Chinese [18].…”
Section: Introductionmentioning
confidence: 99%